Hematopoietic Cell Transplantation for Sickle Cell Disease - Krishnamurti, Lakshmanan (Frontiers in Pediatrics, 2021)
Sickle cell disease (SCD) is a severe autosomal recessively inherited disorder of the red blood cell characterized by erythrocyte deformation caused by the polymerization of the abnormal hemoglobin, which leads to erythrocyte deformation and triggers downstream pathological changes. These include abnormal rheology, vasocclusion, ischemic tissue damage, and hemolysis associated endothelial dysfunction. These acute and chronic physiologic disturbances contribute to morbidity, organ dysfunction, and diminished survival. Hematopoietic cell transplantation (HCT) from HLA-matched or unrelated donors or haploidentical related donors or genetically modified autologous hematopoietic progenitor cells is performed with the intent of cure or long-term amelioration of disease manifestations. Excellent outcomes have been observed following HLA-identical matched related donor (MRD) HCT. The majority of SCD patients do not have an available HLA identical sibling donor. Increasingly, however, they have the option of undergoing HCT from unrelated HLA matched or related haploidentical donors. The preliminary results of transplantation of autologous hematopoietic progenitor cells genetically modified by adding a non-sickling gene or by genomic editing to increase expression of fetal hemoglobin are encouraging. These approaches are being evaluated in early phase clinical trials. In performing HCT in patients with SCD, careful consideration must be given to patient and donor selection, conditioning and GVHD regimen, and pre-HCT evaluation and management during and after HCT. Socio-demographic factors may also impact awareness of and access to HCT. Further, there is a substantial decisional dilemma in HCT with complex tradeoffs between the possibility of amelioration of disease manifestations and early or late complications of HCT. The performance of HCT for SCD requires careful multi-disciplinary collaboration and shared decision making between the physician and informed patients and caregivers.